1992
DOI: 10.1590/s0036-46651992000400012
|View full text |Cite
|
Sign up to set email alerts
|

Parasitismo por Cryptosporidium sp. em crianças com diarréia aguda

Abstract: No período de agosto de 1987 a julho de 1990, examinaram-se, na Seção de Enteroparasitoses do Instituto Adolfo Lutz, 241 amostras de fezes de crianças, com idade variável entre 1 e 48 meses, que apresentavam episódio agudo de diarréia e foram atendidas no Instituto da Criança do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo. Quarenta e duas (17,43%) amostras revelaram a presença de Cryptosporidium sp. após coloração por fucsina-carbólica. O achado de oocistos de Cryptosporidium sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
4

Year Published

2001
2001
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
2
10
1
4
Order By: Relevance
“…3,6,8,10,29 Our study similarly found a significant association between the odds of C. parvum infection and the occurrence of rain (Figure 1). Similar trends were also observed in other regions of Brazil, and in Indonesia and Zambia.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…3,6,8,10,29 Our study similarly found a significant association between the odds of C. parvum infection and the occurrence of rain (Figure 1). Similar trends were also observed in other regions of Brazil, and in Indonesia and Zambia.…”
Section: Discussionsupporting
confidence: 69%
“…7,23 The reported range of cryptosporidial infection in Brazil has varied from 1.1% to 17.4%. 3,[8][9][10][11] Such prevalences were generated by less sensitive diagnostic tests compared with the direct immunofluorescent assay used in our study, [14][15][16][17] but differences in the age distribution of the study population, combined with differences in exposure to risk factors, likely contribute to the inter-study differences in the observed prevalence of infection among Brazilian children. Our adjusted prevalence of 18.7%, which was based on sensitivity data from a gold standard of immunomagnetic separation in combination with immunofluorescent microscopy, 13 was similar to that observed for urban Zambian children 6 and lower than the 29.6% reported for the State of Puebla, Mexico.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations